ظرف الليل و أثره في الجريمة والعقوبة – دراسة في قانون العقوبات الجزائري – " السرقة أنموذجا " - صالحي, لزهر (University of Eloued جامعة الوادي, 2020)
يعتبر ظرف الليل من بين الظروف التي تؤثر على جريمة وعقوبة السرقة، وتأثير هذا الظرف على الجريمة والعقوبة إما لوحده أو مع ظرف آخر، وفي كل حالة حدّد المشرع عقوبة تناسب الجريمة المتأثرة بهذا الظرف، كما أن وصف الجريمة في حدّ ذاتها يتغير من جنحة بسيطة في الأساس إلى جنحة مشددة بتأثير ظرف الليل لوحده، أو جناية إذا كان مع ظرف الليل ظرف آخر يقترن به، ونص المشرع على هذا الظرف الزمني بالضبط، هو لحكمة رآها من أجل حماية أموال الناس وممتلكاتهم Abstract One of the conditions which affects the crime and punishment of theft is the condition of Night . this influence may occur either alone or combined with another condition. In each case the legislator determined an equivalent punishment to the resultant crime. Fundamentally،the level crime lifts from simple to severe fault under the influence of Night s condition alone . or to a crime if the latter is correlated with another condition . Hens the legislator condition purposefully provided on this temporal condition to protect peoples funds and properties .
The Condition of Night and its Impact on Crime and Penalty A Study on the Algerian Law of Penalties " Theft as an Exemplar "
مقال
Keywords: الظرف ، الليل ، العقوبة ، السرقة; condition . Night . the crime . punishment . theft